Essence of Moral Education: Luqman Speaks, the Students Remain Silent? - Syamsuddin, Syamsuddin (ETDC: Indonesian Journal of Research and Educational Review, 2025)
One-way communication between an active teacher/ustaz and passive students can sometimes hinder moral teaching. This study raises important considerations about the effectiveness of internalizing moral ideals, especially for academics who are also students. Is the "Luqman Speaks, the Students Remain Silent" strategy still useful in creating Islamically integrated characters at higher Islamic boarding schools? This study analyzes the nature, implementation, and effectiveness of Ma'had Aly As'adiyah Sengkang's moral education model and determines how communication patterns and student participation affect moral education goals. This study seeks the optimal balance between authoritative transmission (the Luqman model) and student activation. This descriptive qualitative study employs a single case study. The study collected data through participant observation, in-depth interviews with teachers and students, and curriculum document analysis. The results of this study indicate that the practice of moral education at Ma'had Aly As'adiyah Sengkang has shifted from a one-way model to a model that integrates authoritative role models (uswah) with participatory dialogue. Students not only accept but are also encouraged to reflect, discuss, and practice values. However, the disparity between normative understanding and its practical application in daily life persists due to environmental factors and modernization challenges. By developing a comprehensive and contextual moral education paradigm for Islamic boarding school-based higher education institutions, this study contributes to Islamic education theory. The results of this study can be used to evaluate and improve Ma'had Aly As'adiyah Sengkang and comparable institutions' curriculum.